Higher impulsivity and lower grey matter volume in the bilateral prefrontal cortex in long-term abstinent individuals with severe methamphetamine use disorder. (1st July 2020) - Huang, Shucai; Dai, Yuanyuan; Zhang, Changcun; Yang, Chen; Huang, Qiuping; Hao, Wei; Shen, Hongxian
Highlights: The impulsivity and the gray matter volume of the individuals with severe methamphetamine use disorder who have been on abstinence for at least 20 months (SMUD-A) was first explored in this article. Higher impulsivity and lower frontal GMV were found in long-term abstinent individuals with severe methamphetamine use disorder. The impulsivity and right lateral frontal GMV was closely negatively correlated. Abstract: Background: Previous studies have shown that grey matter volume (GMV) might be lower in individuals with methamphetamine use disorder and that dynamic alterations in selected brain regions might appear in individuals after short-term abstinence. However, the GMV of brains in these individuals after long-term abstinence is poorly understood. Moreover, individuals with severe methamphetamine use disorder have been considered to have high levels of impulsivity, but the biological mechanism is still unclear. Methods: In this study, the impulsivity of all participants was assessed using the Barratt Impulsiveness Scale (BIS-11). Using voxel-based morphometry (VBM) in conjunction with statistical parametric mapping on structural magnetic resonance images, the GMVs of the whole brain were compared among 32 drug-naïve healthy controls (HC) and 40 individuals with severe methamphetamine use disorder who had been abstinent for at least 20 months (SMUD-A). Results: We observed significantly higher BIS-11 impulsivity scores and lower GMV in the bilateral superior frontal cortex of SMUD-A individuals than in those of control subjects. The impulsivity score was negatively correlated with GMV in the right superior frontal cortex. Conclusions: These findings offer novel evidence with respect to the impulsivity trait and brain GMV feature in long-term abstinent individuals with severe methamphetamine use disorder. Moreover, our findings suggest that lower GMV in the right superior frontal cortex might reflect a trait marker of higher impulsivity in this population.